Pengembangan Modul Ajar Instalasi Motor Listrik Berbasis Software Zelio logic untuk Meningkatkan Hasil Belajar - Krisna Surya Dwitara; Tri Rijanto; Joko Joko; Ali Nur Fathoni (Indo Publishing, 2026)
This study aims to develop a motor electrical installation teaching module based on Zelio Logic software to improve the learning outcomes of eleventh-grade students in the Electrical Power Installation Engineering program at SMKN 3 Jombang. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 36 students of class XI TITL. The research instruments included material and media expert validation sheets, student response questionnaires, cognitive learning outcome tests, and psychomotor observation sheets. The results showed that the teaching module achieved a very high level of validity, with scores of 90.87% from material experts and 91.79% from media experts. The practicality test result showed a percentage of 82.30%, categorized as very practical. The effectiveness of the module was reflected in the improvement of students’ cognitive learning outcomes, where the average pretest score of 43.47 increased to 81.8 in the posttest, with an N-Gain score of 0.67 categorized as moderate. In addition, students’ psychomotor learning outcomes also improved, with the learning mastery level reaching 86%. Therefore, the Zelio Logic software-based teaching module is proven to be feasible and effective for use in the teaching and learning process of motor electrical installation subjects.